Non-Usury Bank Corporation (NUBankCo): The Solution to Islamic Banking - Bidabad, Bijan (International Journal of Shari’ah and Corporate Governance Research, 2019)
In this paper, we are going to introduce a new Islamic financial institution with elaborated economic and financial characteristics. «Non-Usury Bank Corporation» (NUBankCo) is defined in a way that depositors are the shareholders of the Bank. This corporation is a new kind of shared ownership corporation which its shareholders are deposit holders and their deposits work as corporation’s equities. The defined bank can perform non-usury operations, and by designing a behavioral model, it is shown that NUBankCo can draw an environment that the welfare of society is to be maximized. Mobility of deposit resources in NUBankCo is less than conventional banks, and there are fewer conflicts between large and small shareholders/depositors and limits the emergence of shareholders’ cartels and thus huge sudden outflow of funds which creates bankruptcy crises.OECD’s corporate governance criteria are completely adaptable to this bank. Other pronouncements like Basel, AAOFI, IFSB, and FSF can be applied to this bank. NUBankCo can be established in different countries and can be adapted to different monetary, banking, foreign exchange, and commercial laws and regulations and can coexist in competition with conventional banks.NUbankCo will be Islamic in deposit mobilization side and will be Islamic in the loan/credit side for certain Islamic contracts and banking operations. Foreign currency exchange operations, bonds, commercial papers, and precious metals transactions, cash and draft operations, and credit and beneloan (non-interest loan) operations are characterized for NUBankCo to be fully Islamic.